Copper-manganese bimetallic fiber catalyst as well as preparation method and application thereof

By loading copper manganese ions on the fiber catalyst and performing ozone activation treatment, the problems of low catalytic activity and poor water vapor resistance are solved, and the effect of efficient catalytic ozone oxidation reaction is achieved.

CN119608248APending Publication Date: 2025-03-14HENAN ACADEMY OF SCI CHEM RES INST CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411790525.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-12-11
Filing Date
2024-12-06
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing fiber catalysts have problems with low catalytic activity and poor water vapor resistance when catalyzing ozone oxidation reaction, especially in high humidity conditions, their catalytic performance is significantly reduced.

Method used

The copper-manganese bimetallic fiber catalyst is formed by loading copper and manganese ions on the polymer fibers and calcining in an inert gas atmosphere. This method not only improves the activity of the catalyst, but also enhances its water vapor resistance.

Benefits of technology

The catalytic activity and water vapor resistance of the copper-manganese bimetal fiber catalyst are significantly improved, and can efficiently catalyze ozone oxidation and degradation of benzene in the gas phase under high humidity conditions, with a removal rate of 98.5% to 100%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005175206530000011
    Figure HDA0005175206530000011
  • Figure HDA0005175206530000012
    Figure HDA0005175206530000012
  • Figure HDA0005175206530000013
    Figure HDA0005175206530000013
Patent Text Reader

Abstract

The invention belongs to the technical field of new materials, and discloses a copper-manganese bimetallic fiber catalyst and a preparation method and application thereof.The preparation method specifically comprises the steps that copper ions and manganese ions are loaded on polymer fibers, and copper-manganese-loaded polymer fibers are obtained; s2, roasting the copper-manganese-loaded polymer fiber prepared in the step S1 in an inert gas atmosphere to obtain a copper-manganese bimetallic fiber catalytic material precursor; and S2, carrying out ozone in-situ activation treatment on the copper-manganese bimetallic fiber catalytic material precursor prepared in the step S2 by adopting ozone airflow to obtain the copper-manganese-based fiber catalyst. The prepared catalyst is high in catalytic activity, good in water vapor resistance and high in thermal oxidation stability, in addition, the selection of forms is not limited, the catalyst can be applied in any forms such as disordered fibers, woolen yarns, needle-punched fabrics and knitted fabrics, filling is convenient, and the use depth and range of catalytic materials are greatly widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new materials, and specifically relates to a copper-manganese bimetallic fiber catalyst and a preparation method and application thereof. Background Art

[0002] The research in the field of functionalizing common textile fibers (synthetic fibers and natural fibers) to keep the original characteristics and advantages of the fibers and to have various special properties and uses has attracted increasing attention in recent years. Textile fibers are in sufficient supply, with a wide variety and reasonable prices, and are a good source of raw materials for obtaining new materials. Chemical modification is an important means of functionalizing fibers. Through the chemical reaction of the active chemical groups carried by the fibers with certain molecules or ions, or through the chemical reaction assisted by ultrasound, microwaves or heat, the fibers have new surface chemical properties, thus having new functions such as antistatic, water absorption and moisture retention, adsorption and separation, antibacterial deodorization, and catalysis. Chemical modification can be achieved by using different fibers as raw materials and different treatment methods and processes. Currently, most supported metal oxide catalysts use porous granular materials such as metal oxides or molecular sieves as their substrates. Although the catalysts prepared with these substrate materials have excellent stability and dispersibility, their morphology is not easy to change, making them difficult to fill in industrial applications. In addition, most of the active sites of molecular sieve or metal oxide-based catalysts are located inside the particles. During the actual reaction process, the internal diffusion process has a greater impact on the catalytic performance. At the same time, the particles generated by the reaction are prone to block the catalyst pores, thereby reducing the catalyst activity.

[0003] There are a few public reports on fiber catalysts in the prior art. Taking fiber materials with manganese oxide as an example, the relevant literature reports are listed as follows: The literature "Preparation of fiber-supported manganese oxide catalyst and study on its room temperature formaldehyde degradation performance" (Beijing University of Architecture and Civil Engineering, 2015) uses KMnO4 as a precursor and uses methanol to in-situ reduce KMnO4 to prepare MnO xThe catalyst was loaded on filter cotton (PET) to prepare a manganese oxide-loaded fiber catalyst for formaldehyde degradation; and its oxidative degradation performance of formaldehyde in the air at room temperature was reported. The patent "A method for manufacturing fibers for catalytic oxidative decomposition of cationic dyes" (patent application number: 202010651686.6) uses a solution polymerization method to synthesize polymethacrylate, and then uses wet spinning technology to spin polymethacrylate fibers rich in hydroxyl groups on the surface. Finally, under alkaline conditions, the redox reaction between the hydroxyl groups on the fiber surface and potassium permanganate is used to reduce potassium permanganate to generate manganese oxide, and the hydroxyl groups are oxidized to generate carboxylic acid groups. Based on the complexation between manganese oxide and carboxylic acid groups, manganese oxide is firmly bound to the fiber surface to prepare a manganese oxide-loaded fiber catalyst for catalytic oxidative decomposition of cationic dyes, and its catalytic degradation performance of cationic dyes in aqueous solution is reported. Nevertheless, due to the participation of organic polymer fibers, the active sites of the prepared organic polymer fiber catalyst will be more or less covered by organic fragments or inactive components, but it cannot be activated by high-temperature oxidation like inorganic carriers, resulting in fewer active sites on the prepared fiber surface and serious coverage by organic fragments, resulting in its catalytic activity being significantly lower than that of similar inorganic carrier catalysts. Similarly, although the impregnation calcination method (air atmosphere) is a classic process for preparing supported inorganic catalysts, due to the characteristics of organic polymer fiber carriers, this preparation method cannot be used for the preparation of supported organic polymer fiber catalysts. When the supported organic polymer fiber catalyst is prepared by calcination under an inert gas atmosphere, the organic fragments generated by the partial pyrolysis of the fiber structure will cover the generated active sites, resulting in the inability to prepare a highly active supported organic polymer fiber catalyst. Furthermore, due to the oxidizing property of nitrate precursors, they are not suitable for the preparation of supported organic polymer fiber catalysts by the impregnation and calcination method. Other catalytically active component precursors (sulfates, acetates, etc.) cannot generate a large amount of transition metal oxides with high catalytic activity in an inert gas atmosphere, which also results in the inability to prepare highly active supported organic polymer fiber catalysts. In addition, for manganese-supported organic polymer fiber catalysts, when they are used to catalyze ozone oxidation reactions, their heat oxidation resistance and water vapor resistance need to be further improved; the literature "Duan W, Tang K, Zhao L, et al. MnO xNanoparticle-loaded polyacrylonitrile fibers for efficient catalytic ozonation of toluene[J].Atmospheric Pollution Research, 2024, 15 (5): 102079” The study showed that the polymer fiber carrier was degraded during the catalytic ozone oxidation of toluene using polymer fibers loaded with manganese oxide, and water vapor had an inhibitory effect on its catalytic activity. Therefore, for organic polymer fiber catalysts, when they are used to catalyze ozone oxidation reactions, the catalytic activity and water vapor resistance of the fiber catalyst need to be further improved. Summary of the invention

[0004] In view of the problems and shortcomings in the prior art, the purpose of the present invention is to provide a copper-manganese bimetallic fiber catalyst and a preparation method and application thereof.

[0005] To achieve the purpose of the invention, the technical solution adopted by the present invention is as follows: The first aspect of the present invention provides a method for preparing a copper-manganese bimetallic fiber catalyst, comprising the following steps: S1: loading copper ions and manganese ions on polymer fibers to obtain copper-manganese loaded polymer fibers; S2: placing the copper-manganese-loaded polymer fiber prepared in step S1 in an inert gas atmosphere for calcination to obtain a copper-manganese bimetallic fiber catalytic material precursor; S3: using an ozone gas flow to perform an ozone in-situ activation treatment on the copper-manganese bimetallic fiber catalyst material precursor prepared in step S2 to obtain a copper-manganese-based fiber catalyst.

[0006] According to the above preparation method, preferably, in step S3, the temperature of the ozone in-situ activation treatment is 110-120°C, and the time is 5-8 hours. More preferably, the temperature of the ozone in-situ activation treatment is 110°C, and the time is 7 hours.

[0007] According to the above preparation method, preferably, in the step S3, the concentration of ozone in the ozone gas flow is 10-30 mg / L, and more preferably, the concentration of ozone in the ozone gas flow is 20 mg / L.

[0008] According to the above preparation method, preferably, the mass space velocity of the ozone gas flow during the ozone in-situ activation treatment is 240,000 to 1,200,000 mL / (g·h).

[0009] According to the above preparation method, preferably, in step S2, the calcination temperature is 500-700°C, and the calcination time is 0.2-2h. More preferably, the calcination temperature is 600°C.

[0010] According to the above preparation method, preferably, in step S2, the heating rate of the roasting process is 2-20°C / min; the inert gas flow rate is 100-500ml / min. More preferably, the heating rate of the roasting process is 5-15°C / min and the inert gas flow rate is 200-300ml / min. Most preferably, the heating rate of the roasting process is 10°C / min and the inert gas flow rate is 250ml / min.

[0011] According to the above preparation method, preferably, in step S2, the inert gas is nitrogen.

[0012] According to the above preparation method, preferably, the specific operation of the calcination treatment is: placing the copper-manganese-loaded polymer fiber prepared in step S1 in a tubular furnace, heating it to 500-700° C. in a nitrogen atmosphere, and calcining it for 0.2-2 hours.

[0013] According to the above preparation method, preferably, in step S1, the operation of loading copper ions and manganese ions on polymer fibers is: immersing the polymer fibers in a solution containing copper ions and manganese ions, and drying after immersion to obtain copper-manganese loaded polymer fibers.

[0014] According to the above preparation method, preferably, the copper ion concentration in the solution containing copper ions and manganese ions is 0.1 mol / L to 0.4 mol / L, and the manganese ion concentration is 0.1 mol / L to 0.4 mol / L; the solution containing copper ions and manganese ions is a mixed solution of copper salt and manganese salt.

[0015] According to the above preparation method, preferably, the copper salt is copper sulfate, and the manganese salt is manganese acetate.

[0016] According to the above preparation method, preferably, the impregnation process requires ultrasonic oscillation treatment, the temperature of the ultrasonic oscillation treatment is 20-40° C., the ultrasonic oscillation time is 20-120 min, and the ultrasonic oscillation frequency is 20-50 kHz.

[0017] According to the above preparation method, preferably, the polymer fiber is acrylic fiber or modified acrylic fiber. More preferably, the modified acrylic fiber is acrylic fiber grafted with amino groups, and the amino groups are grafted on the acrylic fiber by reacting a polyamine compound with a -CN group in the acrylic fiber.

[0018] According to the above preparation method, preferably, the preparation method of the acrylic fiber grafted with amino groups is: adding the acrylic fiber to a polyamine compound solution for swelling treatment, reacting at 100-150°C for 1-12 hours after swelling, cooling, washing, and drying after the reaction to obtain the acrylic fiber grafted with amino groups. More preferably, the swelling treatment temperature is 60-80°C, and the swelling treatment time is 4-12 hours.

[0019] According to the above preparation method, preferably, the polyamine compound is one or more of ethylenediamine, diethylenetriamine, triethylenetetramine and polyethylenepolyamine.

[0020] According to the above preparation method, preferably, the dosage of the polyamine compound solution is: 20ml-200ml of the polyamine compound solution is added to every 1g of acrylic fiber for swelling treatment, and the mass fraction of the polyamine compound in the polyamine compound solution is 5-100%.

[0021] According to the above preparation method, preferably, the solvent of the polyamine compound solution is water, ethylene glycol, propylene glycol or glycerol.

[0022] The second aspect of the present invention provides a copper-manganese bimetallic fiber catalyst prepared using the preparation method described in the first aspect.

[0023] According to the above-mentioned copper-manganese bimetallic fiber catalyst, preferably, the copper-manganese bimetallic fiber catalyst is in the form of one or more of fiber, wool, needle-punched cloth, and knitted cloth.

[0024] The third aspect of the present invention provides the use of the copper-manganese bimetallic fiber catalyst described in the second aspect in catalyzing ozone oxidation and degradation of benzene series in the gas phase.

[0025] According to the above application, preferably, the benzene series includes toluene and / or benzene, and the degradation temperature is 70-110° C. More preferably, the degradation temperature is 90° C.

[0026] Compared with the prior art, the present invention has the following positive and beneficial effects: (1) The present invention simultaneously loads copper ions and manganese ions on polymer fibers by ultrasonic impregnation. Moreover, during the impregnation process, the copper ions and manganese ions are adsorbed and uniformly dispersed and fixed on the surface of the polymer fibers through the strong chelation between the functional groups on the surface of the polymer fibers (-NH2, -NH-, etc.) and the copper ions and manganese ions, thereby obtaining copper-manganese-loaded polymer fibers. Subsequently, the copper-manganese-loaded polymer fibers are calcined in an inert gas atmosphere to obtain a copper-manganese bimetallic fiber catalytic material precursor. During the calcination process, redox reactions occur between the functional groups on the surface of the polymer fibers (-NH2, -NH-, etc.) and copper, manganese and sulfate, thereby forming a large number of oxygen vacancies on the surface of the polymer fibers, which is beneficial to improving the catalytic activity of the prepared copper-manganese bimetallic fiber catalyst.

[0027] (2) The present invention performs ozone activation treatment on the copper-manganese bimetallic fiber catalyst material precursor prepared by calcination. During the ozone activation process, the strong oxidizing property of ozone can not only partially oxidize and remove organic debris covering the active sites of the polymer fiber, but also further adjust the morphology of copper and manganese species on the surface of the polymer fiber. Before ozone activation, the copper and manganese elements on the surface of the fiber catalyst do not exist completely in the form of oxides, but coexist with sulfides, sulfates and other species. After ozone activation, the copper and manganese species on the fiber surface are oxidized and exist in the form of oxides, forming a moderate high- and low-valence species doping state, further increasing the oxygen vacancy content, effectively improving the catalytic activity of the copper-manganese bimetallic fiber catalyst, and solving the problem that the catalytic active sites on the surface of the manganese-based polymer fiber catalyst material are covered and the transition metal oxides are not generated in large quantities during the preparation process, resulting in low activity or inactivation of the catalytic material.

[0028] (3) The present invention simultaneously loads copper and manganese on polymer fibers. During the ozone activation treatment, organic fragments are oxidized and removed, and the structure of copper and manganese species changes, forming a clear mutually interlocking composite structure between copper and manganese species on the surface of the polymer fibers. The two species can play a synergistic catalytic role, thereby improving the catalytic activity of the copper-manganese bimetallic fiber catalyst. Moreover, the copper species in the copper-manganese-based fiber catalytic material can provide adsorption sites for benzene series, and in the presence of water vapor, the presence of copper is more likely to catalyze the decomposition of ozone to generate highly oxidizing hydroxyl radicals, thereby improving the catalytic degradation performance of the polymer fiber catalytic material for benzene series. Therefore, the introduction of copper significantly improves the catalytic activity and water vapor resistance stability of the copper-manganese bimetallic fiber catalyst, thereby solving the technical problems of low catalytic activity and poor water vapor resistance of the existing polymer fiber catalytic material when catalyzing the degradation of benzene series gases with high humidity.

[0029] (4) The copper-manganese bimetallic fiber catalyst prepared by the present invention can be used to catalyze the ozone oxidation degradation of pollutants, such as volatile organic compounds, odor pollutants, etc., and when the copper-manganese bimetallic fiber catalyst of the present invention is used to degrade polluted gas with a toluene or benzene concentration of 100 ppm under the conditions of an air velocity of 240,000 mL / (g·h), a reaction temperature of 90°C, an ozone concentration of 3.8-4.5 mg / L, and a relative humidity of 5-10%, the toluene or benzene removal rate reaches 98.5% to 100%. Under the same degradation conditions, when the copper-manganese-based polymer fiber material precursor that has not been activated by ozone is used as a catalyst, the toluene removal rate is only 37% to 49%. Therefore, compared with the process without ozone in-situ activation, the catalytic activity of the copper-manganese bimetallic fiber catalyst prepared by the present invention through ozone in-situ activation treatment is significantly improved.

[0030] (5) The present invention selects copper sulfate and manganese acetate as precursors of catalytically active species, and places the copper-manganese-loaded polymer fiber in an inert gas atmosphere for calcination, which can effectively prevent the copper-manganese-loaded polymer fiber from contacting with oxygen or oxidizing substances (nitrates, etc.) during the high-temperature calcination process, thereby avoiding oxidative damage to the polymer fiber by oxygen or oxidizing substances.

[0031] (6) The copper-manganese bimetallic fiber catalyst prepared by the present invention has high catalytic activity, good water vapor resistance, and high thermal oxidation stability. In addition, there is no restriction on the choice of form, and it can be used in any form such as random fibers, wool yarn, needle-punched cloth, knitted cloth, etc., which is not only convenient for filling, but also greatly broadens the depth and breadth of the use of catalytic materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The SEM characterization images of the copper-manganese bimetallic fiber catalytic material precursor and the copper-manganese bimetallic fiber catalyst prepared in Example 1 of the present invention, wherein a1-a3 are different microscopic scale morphology images of the copper-manganese bimetallic fiber catalytic material precursor, and b1-b3 are different microscopic scale morphology images of the copper-manganese bimetallic fiber catalyst; Figure 2 EDS surface scanning images of the copper-manganese bimetallic fiber catalytic material precursor and the copper-manganese bimetallic fiber catalyst prepared in Example 1 of the present invention; a1 is the SEM morphology image of the EDS surface scanning area of ​​the copper-manganese bimetallic fiber catalytic material precursor, and a2, a3, and a4 are surface scanning images of O, Mn, and Cu elements on the surface of the copper-manganese bimetallic fiber catalytic material precursor, respectively; b1 is the SEM morphology image of the EDS surface scanning area of ​​the copper-manganese bimetallic fiber catalyst, and b2, b3, and b4 are surface scanning images of O, Mn, and Cu elements on the surface of the copper-manganese bimetallic fiber catalyst, respectively; Figure 3 This is a graph showing the degradation effect of toluene in gases with different humidity levels catalyzed by ozone oxidation using copper-manganese bimetallic fiber catalysts;X tol. represents the toluene removal rate, X ozo. represents the ozone decomposition rate, C ozo. It represents the ozone concentration, and Relative humidity represents the relative humidity of the gas. DETAILED DESCRIPTION

[0033] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0034] The following detailed descriptions are all exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the present invention belongs.

[0035] It should be noted that the terms used herein are only for describing specific embodiments, and are not intended to limit exemplary embodiments according to the present invention. In addition, it should also be understood that when the terms "comprise" and / or "include" are used in this specification, it indicates that there are features, steps, operations, parts and / or combinations thereof.

[0036] The experimental methods in the following examples without specifying specific conditions all adopt conventional techniques in the art or follow the conditions recommended by the manufacturers; the reagents or instruments used without specifying the manufacturers are all conventional products that can be purchased commercially.

[0037] Embodiment 1: A method for preparing a copper-manganese bimetallic fiber catalyst, specifically comprising: The commercial acrylic fiber was washed three times with deionized water and dried at 60°C to constant weight. 200 mL of triethylenetetramine was added to a three-necked flask, and then 2 g of pretreated acrylic fiber was weighed and immersed in triethylenetetramine at 60°C for swelling for 12 h, then heated to 150°C for reaction for 3 h, cooled, washed, and dried at 60°C to constant weight to obtain amino fiber, and its exchange capacity was measured to be 5.93 mmol / g; 1 g of the obtained amino fiber was immersed in 50 mL of a mixed solution of copper sulfate and manganese acetate, and the concentrations of copper sulfate and manganese acetate in the mixed solution were both 0.4 mol / L, ultrasonic oscillation at 25℃ for 30min, take out the fiber and squeeze it to 4g, and dry it at 60℃ to constant weight to obtain copper-manganese-carrying amine fiber; take 1g of the obtained copper-manganese-carrying amine fiber and place it in a tubular furnace, pass nitrogen at 250mL / min into the tubular furnace for 60min, then heat it to 600℃ at 10℃ / min, and calcine it at a constant temperature for 0.5h, cool it to room temperature after calcination, seal it and store it to obtain a copper-manganese bimetallic fiber catalytic material precursor. The copper-manganese bimetallic fiber catalytic material precursor is placed in an ozone gas flow with an ozone concentration of 20mg / L, a mass space velocity of 1200000mL / (g·h), and a temperature of 110℃ for in-situ activation for 7h to obtain a copper-manganese bimetallic fiber catalyst. After testing, the copper and manganese contents in the copper-manganese bimetallic fiber catalyst are 144.1mg / g and 112.2mg / g, respectively.

[0038] The copper-manganese bimetallic fiber catalyst and the copper-manganese bimetallic fiber catalytic material precursor prepared in this embodiment were used to catalyze ozone oxidation and degrade toluene in the gas at different temperatures; the degradation experimental conditions were: air velocity 240000 mL / (g·h), toluene concentration in the gas was 100 ppm, ozone concentration was 3.8-4.5 mg / L, and relative humidity of the gas was 5-10%. After the degradation reaction was completed, the toluene content in the gas was detected and the toluene removal rate was calculated.

[0039] It was found through testing that when the reaction temperature of catalytic ozone oxidation degradation of toluene was 90°C, the removal rate of toluene in the gas by the copper-manganese bimetallic fiber catalyst prepared in this embodiment was 100%, while the removal rate of toluene in the gas by the copper-manganese bimetallic fiber catalyst material precursor was 46%. This shows that the catalytic performance of the copper-manganese bimetallic fiber catalyst prepared by the present invention is significantly higher than that of the copper-manganese bimetallic fiber catalyst material precursor that has not been treated with ozone in-situ activation, and can be used to catalyze the oxidation degradation of toluene pollutants in the gas by ozone.

[0040] Embodiment 2: A method for preparing a copper-manganese bimetallic fiber catalyst, specifically comprising: The commercial acrylic fiber was washed three times with deionized water and dried at 60°C to constant weight. 200 mL of diethylenetriamine solution (the mass fraction of diethylenetriamine in the diethylenetriamine solution was 20%, and the solvent of the diethylenetriamine solution was ethylene glycol) was added to a three-necked flask, and then 2 g of pretreated acrylic fiber was weighed and immersed in diethylenetriamine for swelling at 80°C for 4 hours, and then heated to 130°C for reaction for 5 hours, cooled, washed, and dried at 60°C to constant weight to obtain amino fiber, and its exchange capacity was measured to be 4.05 mmol / g; 1 g of the obtained amino fiber was immersed in 30 mL of a mixed solution of copper sulfate and manganese acetate, and the concentrations of copper sulfate and manganese acetate in the mixed solution were 0.2 mol / L and 0.4 mol / L, respectively. mol / L, ultrasonic oscillation at 25℃ for 20min, take out the fiber and squeeze it to 2g, dry it at 60℃ to constant weight, and obtain copper-manganese-loaded amine fiber; take 1g of the obtained copper-manganese-loaded amine fiber and place it in a tubular furnace, pass nitrogen at 250mL / min into the tubular furnace for 60min, then heat it to 700℃ at 20℃ / min, and calcine it at a constant temperature for 1h, cool it to room temperature after calcination, seal it and store it, and obtain the copper-manganese bimetallic fiber catalytic material precursor. The copper-manganese bimetallic fiber catalytic material precursor is placed in an ozone gas flow with an ozone concentration of 30mg / L, a mass space velocity of 240000mL / (g·h), and a temperature of 110℃ for in-situ activation for 5h to obtain a copper-manganese bimetallic fiber catalyst. After testing, the copper and manganese contents in the copper-manganese bimetallic fiber catalyst are 115.9mg / g and 120.3mg / g, respectively.

[0041] The copper-manganese bimetallic fiber catalyst and the copper-manganese bimetallic fiber catalytic material precursor prepared in this embodiment were used to catalyze ozone oxidation and degrade toluene in the gas at different temperatures; the degradation experimental conditions were: air velocity 240000 mL / (g·h), toluene concentration in the gas was 100 ppm, ozone concentration was 3.8-4.5 mg / L, and relative humidity of the gas was 5-10%. After the degradation reaction was completed, the toluene content in the gas was detected and the toluene removal rate was calculated.

[0042] It was found that when the reaction temperature of catalytic ozone oxidation degradation of toluene was 90°C, the removal rate of toluene in the gas by the copper-manganese bimetallic fiber catalyst prepared in this embodiment was 100%, while the removal rate of toluene in the gas by the copper-manganese bimetallic fiber catalyst material precursor was 49%. This shows that the catalytic performance of the copper-manganese bimetallic fiber catalyst prepared by the present invention is significantly higher than that of the copper-manganese bimetallic fiber catalyst material precursor that has not been treated with ozone in-situ activation, and can be used to catalyze ozone oxidation degradation of toluene pollutants in the gas.

[0043] Embodiment 3: A method for preparing a copper-manganese bimetallic fiber catalyst, specifically comprising: The commercial acrylic fiber was washed three times with deionized water and dried at 60°C to constant weight. 40 mL of ethylenediamine solution (the mass fraction of ethylenediamine in the ethylenediamine solution was 40%, and the solvent of the ethylenediamine solution was propylene glycol) was added to a three-necked flask, and then 2 g of pretreated acrylic fiber was weighed and immersed in diethylenetriamine at 60°C for swelling for 12 hours, then heated to 100°C for reaction for 12 hours, cooled, washed, and dried at 60°C to constant weight to obtain amino fiber, and its exchange capacity was measured to be 3.06 mmol / g; 1 g of the obtained amino fiber was immersed in 15 mL of a mixed solution of copper sulfate and manganese acetate, and the concentrations of copper sulfate and manganese acetate in the mixed solution were both 0.1 mol / L, ultrasonic oscillation at 25℃ for 40min, take out the fiber and squeeze it to 6g, dry it at 60℃ to constant weight, and obtain copper-manganese-loaded amine fiber; take 1g of the obtained copper-manganese-loaded amine fiber and place it in a tubular furnace, pass nitrogen at 250mL / min into the tubular furnace for 60min, then heat it to 500℃ at 5℃ / min, and calcine it at a constant temperature for 2h, cool it to room temperature after calcination, seal it and store it, and obtain the copper-manganese bimetallic fiber catalytic material precursor. The copper-manganese bimetallic fiber catalytic material precursor is placed in an ozone gas flow with an ozone concentration of 10mg / L, a mass space velocity of 960000mL / (g·h), and a temperature of 120℃ for in-situ activation for 8h to obtain a copper-manganese bimetallic fiber catalyst. After testing, the copper and manganese contents in the copper-manganese bimetallic fiber catalyst are 106.1mg / g and 85.6mg / g, respectively.

[0044] The copper-manganese bimetallic fiber catalyst and the copper-manganese bimetallic fiber catalytic material precursor prepared in this embodiment were used to catalyze ozone oxidation and degrade toluene in the gas at different temperatures; the degradation experimental conditions were: air velocity 240000 mL / (g·h), toluene concentration in the gas was 100 ppm, ozone concentration was 3.8-4.5 mg / L, and relative humidity of the gas was 5-10%. After the degradation reaction was completed, the toluene content in the gas was detected and the toluene removal rate was calculated.

[0045] It was found through testing that the reaction temperature for catalytic ozone oxidation degradation of toluene is 90°C, and the removal rate of toluene in the gas by the copper-manganese bimetallic fiber catalyst prepared in this embodiment is 98.5%, while the removal rate of toluene in the gas by the copper-manganese bimetallic fiber catalytic material precursor is 42%. This shows that the catalytic performance of the copper-manganese bimetallic fiber catalyst prepared by the present invention is significantly higher than that of the copper-manganese bimetallic fiber catalytic material precursor that has not been treated with ozone in-situ activation, and can be used for catalytic ozone oxidation degradation of toluene pollutants in the gas.

[0046] Embodiment 4: A method for preparing a copper-manganese bimetallic fiber catalyst, specifically comprising: The commercial acrylic fiber was washed three times with deionized water and dried at 60°C to constant weight. 200mL of triethylenetetramine was added to a three-necked flask, and then 2g of pretreated acrylic fiber was weighed and immersed in triethylenetetramine at 60°C for swelling for 12h, then heated to 150°C for reaction for 3h, cooled, washed, and dried at 60°C to constant weight to obtain amino fiber, and its exchange capacity was measured to be 5.93mmol / g; 1g of the obtained amino fiber was immersed in 50mL of a mixed solution of copper sulfate and manganese acetate, and the concentrations of copper sulfate and manganese acetate in the mixed solution were 0.4mol / L and 0.2mol / L, respectively. mol / L mixed solution, ultrasonic oscillation at 25℃ for 30min, take out the fiber and squeeze it to 4g, dry it at 60℃ to constant weight, and obtain copper-manganese-loaded amine fiber; take 1g of the obtained copper-manganese-loaded amine fiber and place it in a tubular furnace, pass nitrogen at 250mL / min into the tubular furnace for 60min, then heat it to 600℃ at 10℃ / min, and calcine it at a constant temperature for 0.5h, cool it to room temperature after calcination, seal it and store it, and obtain the copper-manganese bimetallic fiber catalytic material precursor. The copper-manganese bimetallic fiber catalytic material precursor is placed in an ozone gas flow with an ozone concentration of 20mg / L, a mass space velocity of 720000mL / (g·h), and a temperature of 110℃ for in-situ activation for 7h to obtain a copper-manganese bimetallic fiber catalyst. After testing, the copper and manganese contents in the copper-manganese bimetallic fiber catalyst are 161.7mg / g and 40.5mg / g, respectively.

[0047] The copper-manganese bimetallic fiber catalyst and the copper-manganese bimetallic fiber catalytic material precursor prepared in this embodiment were used to catalyze ozone oxidation and degrade toluene in the gas at different temperatures; the degradation experimental conditions were: air velocity 240000 mL / (g·h), toluene concentration in the gas was 100 ppm, ozone concentration was 3.8-4.5 mg / L, and relative humidity of the gas was 5-10%. After the degradation reaction was completed, the toluene content in the gas was detected and the toluene removal rate was calculated.

[0048] It was found through testing that the reaction temperature for catalytic ozone oxidation degradation of toluene is 90°C, and the removal rate of toluene in the gas by the copper-manganese bimetallic fiber catalyst prepared in this embodiment is 99%, while the removal rate of toluene in the gas by the copper-manganese bimetallic fiber catalytic material precursor is 37%. This shows that the catalytic performance of the copper-manganese bimetallic fiber catalyst prepared by the present invention is significantly higher than that of the copper-manganese bimetallic fiber catalytic material precursor that has not been treated with ozone in-situ activation, and can be used for catalytic ozone oxidation degradation of toluene pollutants in the gas.

[0049] Comparative Example 1: A method for preparing a copper metal fiber catalyst, specifically comprising: The commercial acrylic fiber was washed three times with deionized water and dried at 60°C to constant weight. 200 mL of triethylenetetramine was added to a three-necked flask, and then 2 g of pretreated acrylic fiber was weighed and immersed in triethylenetetramine for swelling at 60°C for 12 h, then heated to 150°C for reaction for 3 h, cooled, washed, and dried at 60°C to constant weight to obtain amino fiber, and its exchange capacity was measured to be 5.93 mmol / g; 1 g of the prepared amino fiber was immersed in 50 mL of copper sulfate solution, the concentration of the copper sulfate solution was 0.4 mol / L, ultrasonically oscillated at 25°C for 30 min, the fiber was taken out and squeezed to 4 g, and dried at 60°C to constant weight to obtain copper-loaded amino fiber; 1 g of the prepared copper-loaded amino fiber was placed in a tubular furnace, nitrogen was passed into the tubular furnace at 250 mL / min for equilibration for 60 min, then the temperature was increased to 600°C at 10°C / min, and constant temperature roasted for 0.5 h, cooled to room temperature after roasting, sealed and stored to obtain a copper metal fiber catalytic material precursor. The copper metal fiber catalyst material precursor was placed in an ozone gas flow with an ozone concentration of 20 mg / L, a mass space velocity of 1200000 mL / (g·h) and a temperature of 110°C for in-situ activation for 7 hours to obtain a copper metal fiber catalyst. After testing, the copper content in the copper metal fiber catalyst was 176.9 mg / g.

[0050] The copper metal fiber catalyst and the copper metal fiber catalytic material precursor prepared in this embodiment were used to catalyze ozone oxidation and degrade toluene in the gas at different temperatures; the degradation experimental conditions were: space velocity 240000 mL / (g·h), toluene concentration in the gas was 100 ppm, ozone concentration was 3.8-4.5 mg / L, and gas humidity was 5-10%. After the degradation reaction was completed, the toluene content in the gas was detected and the toluene removal rate was calculated.

[0051] It was found that the reaction temperature for catalytic ozone oxidation degradation of toluene was 90°C. The removal rate of toluene in the gas by the copper metal fiber catalyst prepared in this embodiment was 65%, while the removal rate of toluene in the gas by the copper metal fiber catalytic material precursor was 32%.

[0052] Comparative Example 2: A method for preparing a manganese metal fiber catalyst, specifically comprising: The commercial acrylic fiber was washed three times with deionized water and dried at 60°C to constant weight. 200 mL of triethylenetetramine was added to a three-necked flask, and then 2 g of pretreated acrylic fiber was weighed and immersed in triethylenetetramine for swelling at 60°C for 12 h, then heated to 150°C for reaction for 3 h, cooled, washed, and dried at 60°C to constant weight to obtain amino fiber, and its exchange capacity was measured to be 5.93 mmol / g; 1 g of the obtained amino fiber was immersed in 50 mL of manganese acetate solution, the concentration of manganese acetate solution was 0.4 mol / L, ultrasonically oscillated at 25°C for 30 min, the fiber was taken out and squeezed to 4 g, and dried at 60°C to constant weight to obtain manganese-loaded amino fiber; 1 g of the obtained manganese-loaded amino fiber was placed in a tubular furnace, nitrogen was passed into the tubular furnace at 250 mL / min for equilibration for 60 min, then the temperature was increased to 600°C at 10°C / min, and constant temperature calcined for 0.5 h, cooled to room temperature after calcination, and sealed for storage to obtain a manganese metal fiber catalytic material precursor. The manganese metal fiber catalyst material precursor was placed in an ozone gas flow with an ozone concentration of 20 mg / L, a mass space velocity of 1200000 mL / (g·h) and a temperature of 110°C for in-situ activation for 7 hours to obtain a manganese metal fiber catalyst. After testing, the manganese content in the manganese metal fiber catalyst was 165.3 mg / g.

[0053] The manganese metal fiber catalyst and the manganese metal fiber catalytic material precursor prepared in this embodiment were respectively used to catalyze ozone oxidation and degrade toluene in the gas at different temperatures; the degradation experimental conditions were: space velocity 240000 mL / (g·h), toluene concentration in the gas was 100 ppm, ozone concentration was 3.8-4.5 mg / L, and gas humidity was 5-10%. After the degradation reaction was completed, the toluene content in the gas was detected and the toluene removal rate was calculated.

[0054] It was found that when the reaction temperature of catalytic ozone oxidation degradation of toluene was 90°C, the removal rate of toluene in the gas by the manganese metal fiber catalyst prepared in this embodiment was 87%, while the removal rate of toluene in the gas by the manganese metal fiber catalytic material precursor was 46%.

[0055] Compared with Comparative Example 1 and Comparative Example 2, the removal rate of toluene by the copper-manganese bimetallic fiber catalyst prepared in Example 1 of the present invention was significantly higher than that of Comparative Example 1 and Comparative Example 2 when catalyzing ozone oxidation and degradation of toluene at 90°C; this indicates that the copper and manganese species in the copper-manganese bimetallic fiber catalyst have a synergistic catalytic effect.

[0056] (I) SEM characterization of the copper-manganese bimetallic fiber catalyst prepared by the present invention The copper-manganese bimetallic fiber catalytic material precursor and the copper-manganese bimetallic fiber catalyst prepared in Example 1 of the present invention were characterized by SEM. Figure 1 shown.

[0057] Depend on Figure 1 It can be seen that there are only some irregularly distributed particles on the fiber surface in the copper-manganese bimetallic fiber catalytic material precursor. After ozone in-situ activation, rod-shaped and snowflake-shaped crystals appear on the fiber surface, and the rod-shaped and snowflake-shaped crystals are closely interwoven and inlaid with different particles on the fiber surface, forming a large number of pore structures, indicating that after ozone activation, the copper species and manganese species on the fiber surface form a mutually embedded composite structure. This is mainly because the ozone in-situ activation causes the organic fragments covering the surface of the active site to be stripped and degraded under autocatalytic ozone oxidation, exposing the active species on the fiber surface, and ozone activation causes the copper and manganese species to exist more in the form of oxides, thereby greatly improving the fiber catalytic performance.

[0058] (II) EDS surface scanning characterization of the copper-manganese bimetallic fiber catalyst prepared by the present invention The copper-manganese bimetallic fiber catalytic material precursor and the copper-manganese bimetallic fiber catalyst prepared in Example 1 of the present invention were subjected to EDS surface scanning. The EDS surface scanning results are as follows: Figure 2 shown.

[0059] Depend on Figure 2 It can be seen that the copper and manganese content on the surface of the copper-manganese bimetallic fiber catalyst material precursor before ozone activation is high and evenly distributed, while the oxygen content is low, indicating that the copper and manganese elements on the surface of the fiber catalyst before ozone activation do not exist completely in the form of oxides, but coexist with sulfides, sulfates and other species. After ozone activation, the distribution density of O, Mn, and Cu elements on the surface of the prepared copper-manganese bimetallic fiber catalyst fiber increased significantly, indicating that ozone activation stripped the organic fragments covering the surface of copper and manganese elements, and more copper and manganese species were oxidized and existed in the form of oxides. The prepared polymer fiber catalyst is a copper-manganese bimetallic fiber catalyst.

[0060] (III) Water vapor resistance stability test of the copper-manganese bimetallic fiber catalyst prepared by the present invention In order to study the water vapor resistance of the copper-manganese bimetallic fiber catalyst prepared in this application, the copper-manganese bimetallic fiber catalyst prepared in Example 1 of the present invention, the copper metal fiber catalyst prepared in Comparative Example 1, and the manganese metal fiber catalyst prepared in Comparative Example 2 were used to catalyze the ozone oxidation degradation of toluene in the gas; the degradation experimental conditions were: air velocity 240000 mL / (g·h), reaction temperature 90°C, toluene concentration in the gas was 100 ppm, ozone concentration was 3.8-4.5 mg / L, and relative humidity of the gas was 90%. After the degradation reaction was completed, the toluene content in the gas was detected and the toluene removal rate was calculated.

[0061] It was found through testing that the removal rate of toluene in the gas by the copper-manganese bimetallic fiber catalyst prepared in Example 1 of the present invention was 100%, while the removal rate of toluene in the gas by the copper metal fiber catalyst prepared in Comparative Example 1 was 68%, and the removal rate of toluene in the gas by the manganese metal fiber catalyst prepared in Comparative Example 2 was 74%. This shows that copper species have excellent water vapor resistance, and the introduction of copper can improve the catalytic activity of the manganese-supported fiber catalyst.

[0062] In addition, in order to further study the effect of different gas humidity on the performance of the copper-manganese bimetallic fiber catalyst of the present invention in catalyzing the ozone oxidation degradation of toluene in the gas, the copper-manganese bimetallic fiber catalyst prepared in Example 1 of the present invention was used to catalyze the ozone oxidation degradation of toluene in gases with different humidity; the degradation experimental conditions were: mass space velocity 480000 mL / (g·h), reaction temperature 90°C, and toluene concentration in the gas was 100 ppm. During the degradation reaction, the contents of toluene and ozone in the gas were detected and the toluene removal rate and ozone decomposition rate were calculated. The experimental results are as follows: Figure 3 shown.

[0063] Depend on Figure 3 It can be seen that within the first 120 min, the relative humidity of the reaction system increased from 13% to 32-36%, and the toluene removal rate and ozone decomposition rate both increased to a certain extent. This was mainly due to the fact that ozone decomposition in the presence of water vapor generated strongly oxidizing hydroxyl radicals, which promoted the oxidative degradation of toluene. Within 120-280 min, the relative humidity continued to increase to 88%-96%, the ozone decomposition rate remained stable, and the toluene removal rate increased to more than 97%. However, due to the simultaneous increase in ozone concentration, the influence of relative humidity could not be proved. min, the ozone concentration remained basically unchanged, and the relative humidity was increased from 68% to 99%, while the toluene removal rate (92-94%) and the ozone decomposition rate remained basically unchanged, indicating that within this relative humidity range, water vapor had no obvious effect on the catalytic activity of the catalyst; after 520 min, the relative humidity was gradually reduced until the relative humidity was reduced to 35%, the toluene removal rate remained basically unchanged (92%), but the ozone decomposition rate decreased from 95% to 91%, indicating that high relative humidity is conducive to the decomposition of ozone, that is, water vapor can promote the decomposition of ozone; the relative humidity continued to be reduced, and the ozone decomposition rate continued to decrease, and reached a stable state when the relative humidity was reduced to 19%. In this process, the toluene removal rate decreased simultaneously, and the reduction was higher than the ozone decomposition rate, indicating that a relative humidity above 19% is more conducive to the removal of toluene and the decomposition of ozone. This is mainly because the decomposition of ozone in the presence of water vapor generates strongly oxidizing hydroxyl radicals, which promote the oxidative degradation of toluene. Therefore, the copper-manganese bimetallic fiber catalyst not only has good water vapor resistance stability, but also water vapor can promote its catalytic performance. Even if the relative humidity is maintained at around 99%, it can still maintain a high catalytic activity.

[0064] The experimental results once again proved that the introduction of copper significantly improved the water vapor resistance stability of manganese-based fiber catalyst materials, and solved the technical problem that when manganese oxide-loaded polymer fiber catalyst materials catalyze ozone oxidation to degrade humid BTEX-containing gases, water vapor inhibits the catalytic activity of polymer catalyst materials, resulting in a low BTEX removal rate.

[0065] Finally, it should be noted that the above embodiments are only preferred embodiments of the present invention, and are not intended to limit the present invention in other forms. Any technician familiar with the profession may use the above technical content as inspiration to make changes or modifications. This is an equivalent embodiment of equivalent changes. However, any simple modification, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the technical concept of the present invention still fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a copper-manganese bimetallic fiber catalyst, characterized in that: The following steps are involved: S1: loading copper ions and manganese ions on polymer fibers to obtain copper-manganese loaded polymer fibers; S2: placing the copper-manganese-loaded polymer fiber prepared in step S1 in an inert gas atmosphere for calcination to obtain a copper-manganese bimetallic fiber catalytic material precursor; S3: using an ozone gas flow to perform an ozone in-situ activation treatment on the copper-manganese bimetallic fiber catalyst material precursor prepared in step S2 to obtain a copper-manganese-based fiber catalyst.

2. The preparation method according to claim 1, characterized in that: In step S3, the temperature of the ozone in-situ activation treatment is 110-120° C., and the time is 5-8 h; the concentration of ozone in the ozone gas flow is 10-30 mg / L, and the mass space velocity of the ozone gas flow during the ozone in-situ activation treatment is 240000-1200000 mL / (g·h).

3. The preparation method according to claim 2, characterized in that: In step S2, the calcination temperature is 500-700°C, the calcination time is 0.2-2h; and the heating rate of the calcination process is 2-20°C / min.

4. The preparation method according to any one of claims 1 to 3, characterized in that: In step S1, the operation of loading copper ions and manganese ions on the polymer fiber is: immersing the polymer fiber in a solution containing copper ions and manganese ions, and drying after immersion to obtain copper-manganese loaded polymer fiber.

5. The preparation method according to claim 4, characterized in that: The impregnation process requires ultrasonic oscillation treatment; the concentrations of copper ions and manganese ions in the solution containing copper ions and manganese ions are both 0.1 mol / L to 0.4 mol / L; the solution containing copper ions and manganese ions is a mixed solution of copper salt and manganese salt.

6. The preparation method according to claim 5, characterized in that: The copper salt is copper sulfate, and the manganese salt is manganese acetate.

7. The preparation method according to claim 6, characterized in that: The polymer fiber is acrylic fiber or modified acrylic fiber; the modified acrylic fiber is acrylic fiber grafted with amino groups, and the amino groups are grafted on the acrylic fiber through the reaction of polyamine compounds and -CN groups in the acrylic fiber.

8. A copper-manganese bimetallic fiber catalyst prepared by the preparation method according to any one of claims 1 to 7.

9. The copper-manganese bimetallic fiber catalyst according to claim 7, characterized in that: The copper-manganese bimetallic fiber catalyst is in the form of one or more of fiber, wool, needle-punched cloth, and knitted cloth.

10. Use of the copper-manganese bimetallic fiber catalyst according to claim 8 or 9 in catalytic ozone oxidation degradation of benzene series in gas phase.

Citation Information

Patent Citations

  • A carbon fiber-based denitration catalyst with in-situ supported array active components and its preparation method

    CN111744470B